Recombinant Nucleoprotein-Based Enzyme-Linked Immunosorbent Assay for Detection of Immunoglobulin G Antibodies to Crimean-Congo Hemorrhagic Fever Virus - Saijo, Masayuki (American Society for Microbiology, 2002)
The full-length nucleoprotein of Crimean-Congo hemorrhagic fever virus (CCHFV; 482 amino acid residues) was expressed as a His-tagged recombinant protein (His-CCHFV rNP) in the baculovirus system. The His-CCHFV rNP was efficiently expressed in insect cells and purified by Ni(2+) column chromatography. Using this substrate, an immunoglobulin G (IgG) enzyme-linked immunosorbent assay (ELISA) was developed. We evaluated the sensitivity and specificity of the IgG ELISA, using serum samples previously determined to be antibody positive or negative by immunofluorescence tests on CCHFV-infected Vero E6 cells. We found very good correlation between the two tests: 87% for the positive sera (13 of 15) and 99% for the negative sera (107 of 108). These results indicate that the new IgG ELISA using His-CCHFV rNP has high sensitivity and specificity for detecting CCHFV antibodies. The CCHF patients' sera with high titers reacted only with the NP fragment containing amino acid residues between 201 and 306 in Western blotting. It is known that amino acid homologies are high in this region among various isolates. Thus, it is expected that this ELISA can detect antibodies not only for Chinese strains of CCHFV but also for other strains circulating in the world. These results suggest that the IgG ELISA system developed with the recombinant CCHFV NP is a valuable tool for diagnosis and epidemiological investigations of CCHFV infections.